PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI PADA SEKOLAH MENENGAH PERTAMA NEGERI AKREDITASI A DI PROVINSI JAWA TIMUR - Herry Widyastono (Balai Besar Guru Penggerak Jawa Timur, 2017)
The aim of this study is to obtain information on the use of Information and Communication Technology (ICT) in teaching and school management in SMP Negeri Accreditation of A in East Java province. The study was conducted in August-September 2016 on SMP Negeri 4 Accreditation of A in East Java province. The study concluded that the ICT has been used in teaching and school management in Junior High School Accreditation in East Java province. The use of ICT in the form of ICT-based learning, blended e-learning, Web-based learning/Blog, assessment based on ICT, ICT labs, class multi-media, digital libraries, and application data base school. The study concluded that the ICT has been used in teaching and school management in Junior High School Accreditation in East Java province. The use of ICT in the form of ICT-based learning, blended e-learning, Web-based learning/Blog, assessment based on ICT, ICT labs, class multimedia, digital libraries, and application data base school. The study recommends that the use of ICT optimized, particularly in terms of: learning in the form of mailing lists/discussion groups, distance learning, virtual world class, assessment of learning outcomes that can be accessed by students and parents, as well as documents and digital library services. AbstrakPenelitian ini bertujuan untuk mendapatkan informasi mengenai pemanfaatan teknologi informasi dan komunikasi (TIK) dalam pembelajaran dan manajemen sekolah di SMP negeri akreditasi A di Provinsi Jawa Timur. Penelitian dilakukan pada bulan Agustus-September 2016, pada empat SMP negeri akreditasi A di Provinsi Jawa Timur. Hasil penelitian menyimpulkan bahwa TIK telah dimanfaatkan dalam pembelajaran dan manajemen sekolah pada sekolah menengah pertama negeri akreditasi A di Provinsi Jawa Timur. Pemanfaatan TIK berupa pembelajaran berbasis TIK, blended e-learning, pembelajaran berbasis Web/Blog, penilaian berbasis TIK, laboratorium TIK, kelas multi media, perpustakaan digital, dan aplikasi data base sekolah. Penelitian merekomendasikan agar pemanfaatan TIK dioptimalkan, terutama dalam hal: pembelajaran dalam bentuk mailing list/grup diskusi, pembelajaran langsung jarak jauh, kelas dunia maya, penilaian hasil belajar yang dapat diakses oleh peserta didik dan orang tua, serta dokumen dan layanan perpustakaan digital.